Cascade synthesis of spirooxindole δ-lactone derivatives through N-aryl hydroxymethylacrylamides with xanthates. Issue 42 (21st October 2015) - Wang, Shucheng; Huang, Xuhu; Wen, Yanzhao; Ge, Zemei; Wang, Xin; Li, Runtao
Abstract: A novel and highly efficient cascade synthesis of spirooxindole δ -lactone derivatives from N -aryl hydroxymethylacrylamides and xanthates in good yields is described. The reaction proceeds through a radical addition/cyclization and ester exchange, in which two new C–C bonds and one C–O bond were formed. Graphical abstract: